2019
DOI: 10.1038/s41598-019-44912-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Light Chain Cardiac Amyloidosis with Heart Failure

Abstract: Cardiac involvement in systemic amyloidosis (AL) occurs in ~50% of all AL patients. However once symptomatic heart failure develops, therapeutic options are limited thereby conferring a poor overall prognosis. The median survival is <6 months when AL patients are untreated for the underlying plasma cell dyscrasia. We thus sought to identify risk factors of increased mortality in treatment - naïve , AL cardiac amyloidosis with heart failure. Patients with biopsy-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
1
31
0
1
Order By: Relevance
“…It has been reported that a favorable response rate to bortezomib and dexamethasone as therapy for MM ranges from 66-90% ( 23 ). However, in patients with AL amyloidosis, once symptoms of heart failure occur, the prognosis is dismal with a median survival of <6 months if the patients remain untreated ( 24 ). Moreover, the severe diarrhea did not improve after chemotherapy initiation in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a favorable response rate to bortezomib and dexamethasone as therapy for MM ranges from 66-90% ( 23 ). However, in patients with AL amyloidosis, once symptoms of heart failure occur, the prognosis is dismal with a median survival of <6 months if the patients remain untreated ( 24 ). Moreover, the severe diarrhea did not improve after chemotherapy initiation in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with very advanced cardiac amyloidosis have been reported to have a poor prognosis, with median survival of approximately 6 months and thus, risk stratification remains important for management [27]. In a prior study of 165 patients with AL amyloidosis, increased cardiac wall thickness, older age, higher NYHA class, BNP, and CRP levels were prognostic indicators for increased mortality [28]. Progressive cachexia has been associated with increased morbidity and mortality in cancer patients and in heart failure patients and thus it was hypothesized that patients with increased BMI would be associated with lower mortality as fat reserve may permit a patient to better withstand the toxic side effects of chemotherapy and the metabolic stress of the disease [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the better feasibility of the AMYLI score, the AL and IWT score could be retrospectively calculated only in 61% and 57% of patients in the original cohort, respectively, and in 75% and 70% of patients in the validation cohort, respectively,. In particular, despite being independently associated to patients' prognosis in AL amyloidosis, 10 RWT represents a quite simplistic parameter of LV geometry, and far more complicated parameters might be needed to track all the different hypertrophic patterns of CA. 11,12 Contrary to the AL and IWT scores, we also not assigned a coefficient to the 2 variables selected, and we tested the same score (RWT*E/e′) in the whole population as well as the haematology and hypertrophy cohort.…”
Section: Discussionmentioning
confidence: 99%